1991
DOI: 10.1111/j.1745-4565.1991.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPETITION OF FOOD BACTERIA WITH LISTERIA MONOCYTOGENES DURING ENRICHMENT CULTURE

Abstract: Thirty‐two foodborne bacterial isolates were tested as potential competitors of Listeria monocytogenes strain LM82 during enrichment because of their resistance to the selective agents in Listeria enrichment and isolation media. Competitive ability of each isolate was classified as weak, moderate, or strong by determining the ratio at which it masked identification of LM82 at an inoculation concentration of 10 colony forming units (CFU)/10 mL of Listeria enrichment broth. Of the competitive isolates identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…To determine the effects of the preenrichment levels of each species, a spontaneous streptomycin-resistant variant of L. monocytogenes strain Scott A (CFSAN-82; FDA, Center for Food Safety and Applied Nutrition, College Park, MD) was used, which allowed the population of L. monocytogenes to be determined by growth on plates containing 200 μg/ml streptomycin sulfate (8,13). L. innocua ARL-Ln-001 was selected to be paired with L. monocytogenes CFSAN-82 because of its apparent lack of inhibitory activity, which was subsequently verified by the deferred antagonism plate assay.…”
Section: Effect Of Preenrichment Species Levelsmentioning
confidence: 99%
“…To determine the effects of the preenrichment levels of each species, a spontaneous streptomycin-resistant variant of L. monocytogenes strain Scott A (CFSAN-82; FDA, Center for Food Safety and Applied Nutrition, College Park, MD) was used, which allowed the population of L. monocytogenes to be determined by growth on plates containing 200 μg/ml streptomycin sulfate (8,13). L. innocua ARL-Ln-001 was selected to be paired with L. monocytogenes CFSAN-82 because of its apparent lack of inhibitory activity, which was subsequently verified by the deferred antagonism plate assay.…”
Section: Effect Of Preenrichment Species Levelsmentioning
confidence: 99%
“…Commonly used selective enrichment formulations do not display absolute species level specificity resulting in competition between L. monocytogenes and non-target background microorganisms (Dailey et al, 2014;Dallas et al, 1991;Tran et al, 1990) and between L. monocytogenes and the non-pathogenic species, Listeria innocua (Besse et al, 2005;Carvalheira et al, 2010;Curiale and Lewus, 1994;Keys et al, 2013;Petran and Swanson, 1993). Competition results in limited growth and ultimately a reduced final population of L. monocytogenes which lowers the overall sensitivity of subsequent detection platforms and hinders recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Although this problem has been reduced by newer selective media, enrichment competition is a critical factor in isolation. Earlier studies with the Food and Drug Administration (FDA) method (Dallas et al 1991) showed that L. monocytogenes may have its growth suppressed and predominance of inhibited during selective enrichment by competing food microflora that are resistant to acriflavin, and nalidixic acid. Antimicrobial activity is usually due to organic acids (lactic, acetic, and formic), diacetyl, hydrogen peroxide, and pH changes (Daeschel 1989;Piard and Dezmazeud 1992a,b).…”
Section: Introductionmentioning
confidence: 99%